2020
DOI: 10.15537/smj.2020.2.24845
|View full text |Cite
|
Sign up to set email alerts
|

Endocrinopathies complicating transfusion-dependent hemoglobinopathy

Abstract: Objectives: To investigate the prevalence and significance of different endocrinopathies in children and adolescents with transfusion-dependent thalassemia and sickle-cell anemia. Methods: This is a descriptive, retrospective study between January 2010 and July 2018 in King Abdulaziz University Hospital, Jeddah, Saudi Arabia. Data was collected through reviewing electronic hospital medical records then filling out data collection sheets and was interpreted through the IBM SPSS Statistics for Windows version 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The high incidence of growth failure, frequently already present preSCT, suggests underlying conditions themselves rather than HSCT may play a large role in growth impairment. Many diagnoses are associated with SS including TM, SCD, Fanconi anemia and several IEI/IEM syndromes [54][55][56][57]. Our study did not show that SS or difference between adult height and MPH was associated with factors as age at HSCT, gender, pubertal stage, diagnosis, GvHD and donor type.…”
Section: Growthcontrasting
confidence: 78%
“…The high incidence of growth failure, frequently already present preSCT, suggests underlying conditions themselves rather than HSCT may play a large role in growth impairment. Many diagnoses are associated with SS including TM, SCD, Fanconi anemia and several IEI/IEM syndromes [54][55][56][57]. Our study did not show that SS or difference between adult height and MPH was associated with factors as age at HSCT, gender, pubertal stage, diagnosis, GvHD and donor type.…”
Section: Growthcontrasting
confidence: 78%
“…Out of the total study of 54 (Age >13 years) subjects, 35.18% (n=19) were found to have hypogonadism, which is higher than the study conducted by Al-Agha et al who showed hypogonadism incidence to be 12.5% (n=15) and affected patients had serum ferritin levels more than 2000 ng/dL. 9 In our study, though no In the above-mentioned studies, no correlation was found between serum ferritin and hypogonadism like our study. Lower prevalence of hypogonadism in above studies is due to better chelation and hyper transfusion.…”
Section: Discussionmentioning
confidence: 54%
“…Endocrinopathies can develop as a result of direct iron deposition into endocrine glands and have been reported in a few studies [ 5 ]. A French cohort study revealed that 14% of DBA patients developed iron-related endocrine or other organ complications, and an Italian cohort study revealed that 23% of DBA patients developed the same [ 1 , 5 , 6 ]. To help minimize these complications, chelation therapy is often initiated.…”
Section: Discussionmentioning
confidence: 99%